0814 Impact Of Maternal Voice On Sleep Of Neonates In The Intensive Care Unit. (27th April 2018) - Shellhaas, R A; Barks, J D; Burns, J W; Hassan, F; Chervin, R D
Abstract: Introduction: About 10% of U.S. newborns require treatment in a neonatal intensive care unit (NICU). The NICU environment, which differs dramatically from the in utero milieu, could influence the development of newborn sleep patterns. Whether NICU environment has differential impact on sleep for preterm versus term newborns, and whether exposure to the mother's voice can modulate that impact, is unknown. Methods: Neonates underwent 12-hour, attended polysomnography in the NICU. Their mothers were recorded reading children's books. This recording was randomized to be played continuously during either the first or second 6-hours of the polysomnogram. Sleep-wake stage distributions, entropy, and EEG power were calculated for each 6-hour block. Quantitative sleep measures were regressed on gestational age (GA), with adjustment for neurological examination (Thompson) sores. Data were compared for epochs with, versus without, the recorded maternal voice playing. Results: For 20 neonates ≥35 weeks gestation at birth, but not 27 born preterm at 33–34 weeks, associations of quantitative sleep measures with increasing GA varied with maternal voice exposure. During the voice recording, among neonates ≥35 weeks gestation, increasing GA was associated with increased percent time awake (R 2 =0.52, p<0.001), increased wakefulness bout duration (R 2 =0.39, p=0.003), decreased overall sleep (R 2 =0.52, p<0.001), decreased REM sleep bouts per hour (R 2 =0.35, p=0.004), and increased sleep-wake entropy (R 2 =0.47, p=0.001). These remained significant after adjusting for Thompson scores (adjusted model R 2 =0.25 to 0.49, each p<0.003). Without the voice recording, none of these associations were significant. EEG power at 2-4Hz and 4-8Hz increased with GA in both age groups (R 2 =0.14 to 0.47, p=0.01 to <0.001); this was not changed by the voice recording. For infants <35 weeks gestation, no other associations emerged between sleep measures and GA or postmenstrual age, during or without the maternal voice recording. Conclusion: NICU patients born at ≥35 weeks gestation, but not more premature neonates, show sleep-wake patterns that appear to respond increasingly with age to enriched maternal voice exposure. Newborns may become progressively more responsive to their mothers' voice as they approach full term. Support (If Any): NIH (R21HD083409; UL1TR000433; UL1TR002240)